Three new species of Niphargidae family added to the list of subterranean amphipods (Crustacea: Amphipoda) in Slovenia - Cene Fišer; Teo Delić; Maja Zagmajster (Natura Sloveniae)
Since the last comprehensive checklist of amphipods in 2021, three new species of subterranean amphipods have been confirmed for Slovenia: Niphargus danielopoli, N. lurensis and N. julius. Identification of all three species was based on molecular comparative analyses of the mitochondrial CO1 gene fragment, usually used in DNA barcoding identification. With these additions, we reached a total of 201 amphipod species confirmed for Slovenia, 60 of which are groundwater inhabitants, with 57 species belonging to the genus Niphargus.